MANAJEMEN PENGELOLAAN TOILET UMUM DI DAYA TARIK WISATA KUTA LOMBOK TENGAH - Ni Luh Sueni Widyanti; Maya Aulia Anggreni; I Nengah Juni Sumardiana; Hendri Yasti; Rizal Kurniansah (Sekolah Tinggi Pariwisata Mataram, 2020)
In Kuta Lombok tourist destination, adequate supporting facilities are needed, one of which is public toilets, public toilets which are an important part of the needs of tourists, for that we need good maintenance needs to provide a sense of comfort for tourists. The purpose is to find out the management of public toilets in the tourist attraction of central Lombok Lombok and the management of public toilet management. Data collection methods are interviews, observation and documentation. The results of research conducted on public toilets in the tourist attraction of Kuta Lombok are still not running optimally. This is evident that there are still toilets that do not meet hygiene and sanitation standards. In its management there needs to be a close collaboration between the government and the community so that the management of public toilets goes well. Based on the results of this study it can be concluded that the management of public toilets in the tourist attraction of Kuta Lombok is not going well.